Confirmation of Climate Change in Southwestern Nigeria through Analysis of Rainfall and Temperature Variations over the Region - J. O., Adepitan; E. O., Falayi; F.O., Ogunsanwo (Covenant Journal of Physical and Life Sciences, 2017)
Understanding the variability of precipitation and temperature of a region over a long period gives one an idea about the climate and climate change of such region. The study investigated rainfall and temperature variability in four meteorological stations, namely, Abeokuta (lat.7.01o N, long.3.2oÂ E, alt. 67m) , Ibadan (lat.7.43o N, long.3.9o E, alt. 227m), Ikeja (lat.6.58o N, long.3.33o E, alt. 39m )Â and Ondo (lat.7.1o N, long.4.83o E , alt. 287m) in the south-western region of Nigeria.Monthly rainfall, minimum temperature and maximum temperature data were obtained from Nigeria Meteorological Agency (NIMET) for the period of thirty one years (1980 to 2010) for the study.Descriptive Statistics were deployed to determine the mean, confidence levels, coefficient of kurtosis, skewness and coefficient of variations. A fairly â€œM-shapedâ€ pattern was observed in the monthly mean rainfall distribution with bi-modal peaks in June and September, with slight dryness experienced in August, referred to as â€œAugust breakâ€. Analyses of annual trends over a long period revealed a sequence of alternately decreasing and increasing trends in mean annual rainfall and air temperature in region. Generally however, gradients of the trend lines are positive. There is a negative relationship between annual total rainfall and annual average temperature.